Demineralized Freeze-Dried Bovine Cortical Bone: Its Potential for Guided Bone Regeneration Membrane - David B. Kamadjaja; Achmad Harijadi; Pratiwi Soesilawati; Eny Wahyuni; Nurul Maulidah; Akhsanal Fauzi; Fika Rah Ayu; Roberto Simanjuntak; R. Soesanto; Djodi Asmara; Andra Rizqiawan; Peter Agus; et al. (International Journal of Dentistry)
Background. Bovine pericardium collagen membrane (BPCM) had been widely used in guided bone regeneration (GBR) whose manufacturing process usually required chemical cross-linking to prolong its biodegradation. However, cross-linking of collagen fibrils was associated with poorer tissue integration and delayed vascular invasion. Objective. This study evaluated the potential of bovine cortical bone collagen membrane for GBR by evaluating its antigenicity potential, cytotoxicity, immune and tissue response, and biodegradation behaviors. Material and Methods. Antigenicity potential of demineralized freeze-dried bovine cortical bone membrane (DFDBCBM) was done with histology-based anticellularity evaluation, while cytotoxicity was analyzed using MTT Assay. Evaluation of immune response, tissue response, and biodegradation was done by randomly implanting DFDBCBM and BPCM in rat’s subcutaneous dorsum. Samples were collected at 2, 5, and 7 days and 7, 14, 21, and 28 days for biocompatibility and tissue response-biodegradation study, respectively. Result. DFDBCBM, histologically, showed no retained cells; however, it showed some level of in vitro cytotoxicity. In vivo study exhibited increased immune response to DFDBCBM in early healing phase; however, normal tissue response and degradation rate were observed up to 4 weeks after DFDBCBM implantation. Conclusion. Demineralized freeze-dried bovine cortical bone membrane showed potential for clinical application; however, it needs to be optimized in its biocompatibility to fulfill all requirements for GBR membrane.